Rebooting Trafficking - de Villiers, Nicholas (Anti-Trafficking Review, 2016)
While popular psychology and appeals to emotion have unfortunately dominated discussions of ‘sex trafficking’, this article suggests that feminist psychoanalytic film theory and theories of affect are still useful for making sense of the appeal of sensational exposés like Lifetime Television’s Human Trafficking (2005). The dynamic of identification with (and impersonation of) a human trafficking ‘victim’ by the rescuing Immigration and Customs Enforcement agent (Mira Sorvino) is particularly worthy of scrutiny. Film theory about the ‘rebooting’ of film franchises (iconic brands like Batman) also helps explain the preponderance of similar programming—Sex Slaves (2005), Selling the Girl Next Door (2011), Trafficked (2016)—and the way contemporary discourses of human trafficking have effectively rebranded the myth of ‘white slavery’.